Regional Integration as Diplomacy - Schiff, Maurice (World Bank, 2013)
Regional integration agreements are examples of second-best policies and have an ambiguous impact on welfare. This article builds a model in which regional integration agreements unambiguously raise welfare by correcting for externalities. It assumes that trade between neighboring countries raises trust between them and reduces the likelihood of conflict. The optimum intervention in that case is a subsidy on imports from the neighbor. The article shows that an equivalent solution is for the neighboring countries to tax imports from the rest of the world that is, to form a regional integration agreement together with some domestic taxes. The article shows that (1) the optimum tariffs on imports from the rest of the world are likely to decline over time; (2) deep integration implies lower optimum external tariffs if it is exogenous; (3) optimum external tariffs are higher before deep integration and lower thereafter if deep integration is endogenous; and (4) enlargement of bloc size (in terms of symmetric countries) has an ambiguous impact on external tariffs but raises welfare, and some form of domino effect exists.